2010
DOI: 10.1039/c003389h
|View full text |Cite
|
Sign up to set email alerts
|

Quantum coherence and its interplay with protein environments in photosynthetic electronic energy transfer

Abstract: Recent experiments suggest that electronic energy transfer in photosynthetic pigment-protein complexes involves long-lived quantum coherence among electronic excitations of pigments. [Engel et al., Nature, 2007, 446, 782-786.] The observation has led to the suggestion that quantum coherence might play a significant role in achieving the remarkable efficiency of photosynthetic light harvesting. At the same time, the observation has raised questions regarding the role of the surrounding protein in protecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
455
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(470 citation statements)
references
References 118 publications
12
455
2
1
Order By: Relevance
“…This idea found further support in a subsequent series of measurements that showed spectral beatings for cryptophyte algae [3] and Photosystem II protein complexes [9], indicating that coherent behavior in biological systems is ubiquitous. For FMO, the oscillations were found to persist for hundreds of femtoseconds at ambient temperatures and even up to a few picoseconds at 77 K [10].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…This idea found further support in a subsequent series of measurements that showed spectral beatings for cryptophyte algae [3] and Photosystem II protein complexes [9], indicating that coherent behavior in biological systems is ubiquitous. For FMO, the oscillations were found to persist for hundreds of femtoseconds at ambient temperatures and even up to a few picoseconds at 77 K [10].…”
Section: Introductionmentioning
confidence: 69%
“…The signatures of vibronic coupling in multidimensional spectroscopy have drawn great interest lately, in particular to interpret oscillatory transients observed for light-harvesting complexes [3,[8][9][10] that persist much longer than predicted electronic dephasing times [11].…”
Section: Resultsmentioning
confidence: 99%
“…If the correlation function of the site energy is a delta function (HSR model), absorption and fluorescence lineshapes become Lorentzian so that the Franck-Condon factor is an overlap of two Lorentz functions (eq 14). On the other hand, if the corre- lation function is exponential like the Kubo-Anderson model, lineshapes are closer to the Gaussian [69]. It follows that the KA model gives larger overlap between the donor absorption and the acceptor fluorescence spectra.…”
Section: Exciton Diffusion Within the Rollmentioning
confidence: 90%
“…The reason that efficiency of this process is so high in living plants, is that the entire process of transmitting solar energy inside the leafs takes place under the conditions in which the energy remains in a quantum state. Quantum coherence in electron transfer in photosynthesis lasts for a long time (600 fs) in the pigment-protein complex (Engel, 2007;Ishizaki, 2010). But it is not yet fully known how this coherence is brought about in living tissue, although it has been shown that environmental noise increases energy delivery efficiency (Panitchayangkoona, 2010;Collini, 2010).…”
Section: Photosynthesismentioning
confidence: 99%